2017
DOI: 10.1111/ocr.12210
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nickel‐titanium springs vs elastomeric chains in orthodontic space closure: A systematic review and meta‐analysis

Abstract: The aim of this study is to explore the effectiveness of nickel titanium closing springs (NiTi-CS) and elastomeric power chains (EPC) in orthodontic space closure and to assess the adverse periodontal effects, cost efficiency and patient-centred outcomes between both of these methods. Methods: An electronic search of online databases (Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, Scopus, LILACS and Web of Science), reference lists and grey literature as well as hand search were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
1
35
0
8
Order By: Relevance
“…Many techniques [ 20 ] [ 21 ] [ 22 ] are available to perform retraction of the canine in the extraction space regarding anchorage preparation and the force used of retraction (amount, direction, and force decay). Standardization of the technique of canine retraction was a must so, the use of mini-screws was decided as a direct anchor for retraction of the canine as well as closing coil spring was used providing continuous 150 g of force for canine retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques [ 20 ] [ 21 ] [ 22 ] are available to perform retraction of the canine in the extraction space regarding anchorage preparation and the force used of retraction (amount, direction, and force decay). Standardization of the technique of canine retraction was a must so, the use of mini-screws was decided as a direct anchor for retraction of the canine as well as closing coil spring was used providing continuous 150 g of force for canine retraction.…”
Section: Discussionmentioning
confidence: 99%
“…In several in vivo studies, NiTi springs have been shown to provide faster and more reliable space closure, and that is consistent with our research. It is believed that retaining a constant force over a certain period of time contributes most to their efficiency [16,32].…”
Section: Discussionmentioning
confidence: 99%
“…U nekoliko in vivo studija NiTi opruge su pokazale da obezbeđuju brže i pouzdanije zatvaranje prostora, što je u skladu sa ovim istraživanjem. Smatra se da zadržavanje konstantne sile kroz određeni period najviše doprinosi njihovoj efikasnosti [16,32].…”
Section: Diskusijaunclassified
“…Today, we face new literature, and perhaps the systematic review by Mohammed et al 7 is a game changer. Besides the fact that it compares NiTi coils springs with elastomeric chains instead of active tiebacks, this systematic review is worth looking into in detail.…”
mentioning
confidence: 99%